ANALISIS KONVERGENSI DAN FAKTOR-FAKTOR YANG MEMPENGARUHI PDRB PERKAPITA ANTAR PROVINSI DI INDONESIA - Lutfi Wahyu Hutama (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
ABSTRACT The economic disparity is the main issues regional development in Indonesia. This is because eachregions has different potentials, conditions, and characteristics that vary from one another, causingdisparity between regions. The purpose of this research are : (1) Analyzing the convergenceprocess of GDRP per capita growth rate between provinces in Indonesia. (2) Identifying all thefactors that influencing the convergence process of GDRP per capita growth rate betweenprovinces in Indonesia. This research has done by using secondary data of 2011-2016 period thathas been analyzed by panel data of Sys-GMM. The result of this research is showing us theconvergence process happened for years the analysis period being done but the speed rate is slow,the speed of conditional convergence GDRP per capita is about 3,14%. Based on the estimationresult, the variable are : The Total of Electricity Consumer, The Average Of School Duration, TheMinimum Wage per Province has influenced a significance growth rate of GDRP per capita andspeed up the convergence process. While the Population Density variable, Net Export, and PMTBhas negative influence slowing down the growth rate GDRP per capita and the convergenceprocess. The sigma convergence process analysis shows a fluctuate result with a down trend.Kata kunci : convergence, GDRP per capita, regional economic growth, panel data GMM